Arabic Visual Communication Patterns in Pondok Modern Rahmatul Asri Islamic Boarding School - Tahir , M Hijaz; Hermansyah , Sam (Journal International Dakwah and Communication, 2021)
Islamic boarding schools are currently an alternative choice in continuing education. Since the introduction of the Islamic boarding school system to Indonesia, Islamic boarding schools have entered Indonesia continues to grow. Thus giving rise to the paradigm of the santri graduate of own theirs own mark, Which depend on That profit or characteristics from boarding school education. One of them is the Rahmatul Asri Maroangin Modern Pondok, Maiwa District, Enrekang Regency, South Sulawesi, Which is famous For That superiority from his student by communicate in the Arab. This cottage, known as Rahmatul Asri, was founded in 1996, and has a difference system from other pesantren. Arabic and English are tools for socializing interaction in everyday life. Students which just enter Rahmatul Asri is NO exception. For this reason, from this research it is expected to be able to understand self-concept, namely symbolic object meaning, symbolic action meaning, and shared meaning between That resident from That cottage, Which is be delivered through visual communication